Effectiveness of telesimulation on cardiorespiratory arrest for nursing students - Morais Soares, Francisco Mayron; Kélen Lima, Gleiciane; Batista Mesquita, Kirley Kethellen; de Souza Maciel Ferreira, José Erivelton; Nascimento da Silva, Maria Jocelane; Nunes de Miranda, Francisco Arnoldo (Investigación y Educación en Enfermería, 2023)
Objective. To evaluate the effectiveness of telesimulation on cardiorespiratory arrest to improve the performance of nursing students. Methods. This was an experimental study, whose sample consisted of 30 undergraduate nursing students from a Brazilian university. It was structured from two groups: an experimental (n=15) and a control (n=15). For both groups, expository classes and skills training were held. For the experimental group, a virtual clinical simulation scenario was implemented. Before the beginning of the interventions, a pre-test was applied and, after the end of this, a post-test was applied to evaluate the students ; gain of knowledge and skills. Results: From the analysis of the total correct answers and the scores obtained in the pre-test and post-test, it was found that there was an improvement in the performance of both study groups. Regarding the averages of the points obtained, there was a statistically significant difference between the groups (p=0.001). The post-test score was significantly higher than the pre-test score in the intervention group (p=0.001). Conclusion. The virtual scenario developed proved to be superior in improving the performance of nursing students in managing cardiorespiratory arrest when compared to traditional teaching methods.